Perbedaan Usia, Status Gizi, Frekuensi Minum Kopi dan Asupan Kalsium Pada Pasien Osteoporosis dan Non Osteoporosis di Poli Rawat Jalan RS Ortpedi Prof. Dr. R. Soeharso Surakarta - Musthofiyah, Ayyun, Elida Soviana, S.Gz., M.Gizi, dr. Listiana Darmawati, M.Si (2016)
Background : Osteoporosis is one of the degenerative disease that has become a health problem in Indonesia. Osteoporosis has an impact on the elderly, such as at risk to get a fracture, leading to disability, dependency on others, psychological disorders as well as, increase in mortality. Purpose : The purpose of this research was to know the differences in age, nutritional status, the frequency of drinking coffee and calcium intake between osteoporosis and non-osteoporosis outpatients at poly Ortopedi Prof. Dr. R. Soeharso Surakarta. Method : The research used observational method with cross-sectional approach. The number of subjects was 15 osteoporosis patients and 15 non osteoporosis patients, obtained through consecutive sampling from all patients who met the criteria of inclusion and exclusion. The age and frequency of drinking coffee was obtained from interview with the subjects. Nutritional status data were obtained by measuring weight and height with Body Mass Index (BMI). Calcium intake data were obtained through semi-quantitative FFQ. Statistical tests used the independent T- Test. Data of the subjects osteoporosis or non-osteoporosis were obtained from T- value result of Bone Mineral Density (BMD) examination. Result : Underweight in osteoporosis group was 20%,with the average of BMI was 22,3 ± 4,01 kg/m2. Frequency of drinking enough coffee in osteoporosis patients amounted to 93,3% with an average of 0,6 ± 0,9 a cups and low calcium intake osteoporosis patients was 86,7% with an average of 854,1 ± 92,1 mg. Difference tests between variables; age, nutritional status, the frequency of drinking coffe and calcium intake showed p value 0,132; 0,049; 0,577; and 0,648 respectively. Conclusion : There was a deference in nutritional status between osteoporosis and non-osteoporosis patients. There was no deferences between the frequency of drinking coffee and calcium intake between osteoporosis and non-osteoporosis patients.